Análisis del estrés laboral en el personal de enfermería de una clínica en el distrito de Riohacha (2023)
Currently, The phenomenon of work stress is global in nature, as it has high prevalence rates, which makes it a public health problem due to the effect it generates in different aspects such as economic, social, political and health. Which manifests itself in multiple ways either through mood disorders (low motivation and irritability) in behavior (self-medication, alcohol) in social performance and physical symptoms.